Factors that influence the sustainability of structured allied health journal clubs: a qualitative study - Wenke, Rachel (BMC Med Educ, 2019)
BACKGROUND: Structured journal clubs are a widely used tool to promote evidence-based practice in health professionals, however some journal clubs (JC) are more effectively sustained than others. To date, little research has provided insights into factors which may influence sustainability of JCs within health care settings. As part of a larger randomised controlled study, this research aimed to gain understanding of clinicians’ experiences of sustaining a structured JC format (TREAT- Tailoring Research Evidence and Theory) within their clinical context. The study also aimed to identify which strategies may assist longer term sustainability and future implementation of the TREAT format. METHODS: We employed a qualitative methodology, informed by behaviour change theory. Clinicians (n = 19) from five different JCs participated in focus groups to explore their experience in sustaining the JC format six months after the formal trial period had completed. Clinicians were asked to describe factors which they perceived helped or hindered sustaining components of the JC format within their local context. Following a descriptive summary of the data, barriers and enablers were thematically analysed according to behaviour change theory domains: capability, motivation and opportunity and further mapped to targeted implementation strategies. RESULTS: Participants reported perceived benefits of maintaining the TREAT format and described several components that promoted its sustainability. Sustaining factors linked to individuals’ capability included building research knowledge and skills and having access to research experts. Sustaining factors that enhanced opportunities for behaviour change included management expectation to attend and a team culture which values evidence based practice, while factors found to enhance individuals’ motivation included the JC having close application to practice and clinicians sensing ownership of the JC. Several implementation strategies to enhance these factors are described including graduated support to clinicians in facilitation of JCs and greater engagement with managers. CONCLUSIONS: Long-term sustainability of a structured JC is dependent on both individual and service level factors and a balance of implementation strategies that enhance capability, opportunity and motivation. Consideration of how clinicians can be engaged to take ownership and build their own capability from the commencement of the JC is important. TRIAL REGISTRATION: ACTRN12616000811404. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12909-018-1436-3) contains supplementary material, which is available to authorized users.